SYSTEM SIGNATURE AND RELIABILITY OF COHERENT SYSTEM UNDER CIRCULAR STRESS - Halisdemir, Nurhan (Vinca Inst Nuclear Sci, 2019)
The concept of the system signature is a useful tool not only in the analysis of engineering systems but also in comparing systems of different size. The system signature is a vector that is defined based on the failure of the components in the system and depends only on the design of the system. This article deals with the computation of signature vectors of coherent systems when systems are exposed to a circular stress. We also present how to compare coherent systems under circular stress.
Keywords: system signature; coherent system; circular stress